RELATIONSHIP BETWEEN NEUTROPHIL - LYMPHOCYTE RATIO AND DECREASED GLOMERULAR FILTRATION RATE IN DIABETIC NEPHROPATHY - Asriyani Azikin; Fitriani Mangarengi; Uleng Bahrun (Indonesian Association of Clinical Pathologist and Medical laboratory, 2018)
Diabetic nephropathy is one of the fairly severe Diabetes Mellitus (DM) complications and the main cause of renal failure that can result in mortality. Hyperglycemia in DM induces kidney injury that may result in hemodynamic and metabolic alterations, endothelial dysfunction and inflammatory cells activation. A persistent and continuous inflammation is observed in diabetic nephropathy. One of the inflammation process progression indicators is Neutrophil-Lymphocyte Ratio (NLR). To find out the relationship between NLR and decreased Glomerular Filtration Rate (GFR) in diabetic nephropathy. This study was an observational study with a retrospective approach. This study was conducted in Clinical Pathology Laboratory Installation and Medical Record Installation of Dr. Wahidin Sudirohusodo Makassar Hospital by collecting the patient’s data during February 2015 to February 2016. Patients that were diagnosed as type 2 DM without diabetic nephropathy complication were taken as control and those diagnosed as type 2 DM with diabetic nephropathy were treated as study subjects. One hundred and thirteen (113) samples met the inclusion criteria, consisting of 73 diabetic nephropathy patients with Chronic Kidney Disease (CKD) 13 diabetic nephropathy patients without CKD and 27 type 2 DM patients without diabetic nephropathy complication. Patients consisted of 57 males (50.4%) and 56 females (49,6%). Neutrophil-lymphocyte ratio and GFR values in the group of diabetic nephropathy without CKD were 2.03±0.68 and 85.38±24.63, respectively. Whereas, the NLR and GFR values in control group were 1.74±0.54 and 90.03±28.60, respectively. In the group of diabetic nephropathy with CKD, NLR value increased by 3.19±1.83 and GFR decrease by 30.54±16.45. Spearman test indicated a significant relationship between NLR increase and decreased GFR (r = -0.635, p=0.00). There is a significant relationship between NLR increase and decreased GFR in patients with diabetic nephropathy.